Levels of Human Erythrocyte Membrane-Bound and Cytosolic Glycohydrolases Are Associated with Oxidative Stress in Erectile Dysfunction Patients. (4th August 2014) - Massaccesi, L.; Melzi d'Eril, G. V.; Colpi, G. M.; Tettamanti, G.; Goi, G.; Barassi, A.
Abstract : Oxidative stress (OS) and production of NO, by endothelium nitric oxide synthetase (eNOS), are involved in the pathophysiology of erectile dysfunction (ED). Moreover, OS induces modifications of the physicochemical properties of erythrocyte (RBC) plasma membranes and of the enzyme content of the same membranes. Due to their role in signalling early membrane alterations in OS-related pathologies, several plasma membrane and cytosolic glycohydrolases of human RBC have been proposed as new markers of cellular OS. In RBC, NOS can be activated and deactivated by phosphorylation/glycosylation. In this regulatory mechanism O- β -N-AcetylGlucosaminidase is a key enzyme. Cellular levels of O-GlcNAcylated proteins are related to OS; consequently dysfunctional eNOS O-GlcNAcylation seems to have a crucial role in ED. To elucidate the possible association between RBC glycohydrolases and OS, plasma hydroperoxides and antioxidant total defenses (Lag-time), cytosolic O- β -N-AcetylGlucosaminidase, cytosolic and membrane Hexosaminidase, membrane β -D-Glucuronidase, and α -D-Glucosidase have been studied in 39 ED patients and 30 controls. In ED subjects hydroperoxides and plasma membrane glycohydrolases activities are significantly increased whereas Lag-time values and cytosolic glycohydrolases activities are significantly decreased. These data confirm the strong OS status in ED patients, the role of the studied glycohydrolases as early OS biomarker and suggest their possible use as specific marker of ED patients, particularly in those undergoing nutritional/pharmacological antioxidant therapy.